STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMP NURUL ISLAM KELURAHAN GARUNTANG KECAMATAN BUMI WARAS KOTA BANDAR LAMPUNG - Anisari, Anisari; Purwanti, Eri; Masrur, Moh. (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
The purpose of this study was to determine the strategy Principal in improving the quality of learning in junior Nurul Islam Village Garuntang Earth Sane District of Bandar Lampung.Data analysis is descriptive qualitative analysis that emphasizes the meaning, reasoning, the definition of a given situation (in certain contexts) and describes what about the behavior of the object being studied. Data collector is observation, interview and documentation. As for the conclusions using inductive thinking approach is thought that departs from the facts or specific events later on the facts particular to be withdrawn generalizations that have common properties.Results and analysis can be concluded that the Headmaster had carried out various strategies to enhance the quality of learning in junior Nurul Islam Village Garuntang District of Earth Sane Bandar Lampung that motivate teachers to be creative and innovative in teaching and learning, include teacher training activities, workshops, seminars and others to increase the knowledge and insights of teachers in education, emphasized discipline in terms of utilization of time learning, creation of learning tools and clothing, supervision (supervision) in the preparation of learning tools as well as in the implementation of learning in the classroom and additional hours of special lessons for the subjects of Islamic education because material is vast.